Pembiasaan Mufrodat Pagi dalam Melatih Kemampuan Bilingual (Indonesia, Arab) pada MI Miftahul Huda Ngadireso Poncokusumo Malang - Dhujjah, Nurul Ilmi Badrud; Asfia, Anadila Shinta; Lestari, Arrum Puji; Khasanah, Nur Nisa’atul (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2024)
It is necessary to get used to the Arabic mufrodat which is carried out every morning before lessons start, because the Arabic language environment in elementary schools is a habit found in elementary schools and Madrasah Ibtidaiyah. In this research, the action method was used. This means that researchers conduct research reflectively and collectively in social environments to improve social thinking. The aim of this research is to increase thought and fairness in the actions of researchers in social education. The habit of Arabic mufrodat at Madrasah Ibtidaiyah is the subject of this research. The research results show that mastery of the ability to speak and write Arabic, known as maharah kitabah, maharah istima', maharah qira'ah, and maharah kalam, is very important for learning to speak and use the language. Apart from that, mufrodat learning is also taught through singing because singing can create a fun and entertaining learning atmosphere. This allows students to easily receive and learn the teacher's lessons quickly. So that many schools or other communities outside Ngadireso Village see and admire the morning mufrodat habituation program and consider MI Miftahul Huda as language school.